2019
DOI: 10.1021/acsomega.9b00825
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Nanovesicles for Efficient Encapsulation of Staphylococcal Antibiotics

Abstract: Liposomes are attractive vehicles for localized delivery of antibiotics. There exists, however, a gap in knowledge when it comes to achieving high liposomal loading efficiencies for antibiotics. To address this issue, we investigated three antibiotics of clinical relevance against staphylococcal infections with different hydrophilicity and chemical structure, namely, vancomycin hydrochloride, teicoplanin, and rifampin. We categorized the suitability of different encapsulation techniques on the basis of encapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…The production of liposomes involved multiple steps in a complex and precise process that has a critical impact on the final liposome characteristics, such as size, stability, and functionality of the finished liposomes [ 11 , 12 ]. The more adequate method for liposome production and drug encapsulation also depends on the physicochemical characteristics of the drugs to be encapsulated [ 13 ]. The ethanol injection method is commonly used to produce liposomes, due to its simplicity, ease of scale-up, and safe production technique.…”
Section: Introductionmentioning
confidence: 99%
“…The production of liposomes involved multiple steps in a complex and precise process that has a critical impact on the final liposome characteristics, such as size, stability, and functionality of the finished liposomes [ 11 , 12 ]. The more adequate method for liposome production and drug encapsulation also depends on the physicochemical characteristics of the drugs to be encapsulated [ 13 ]. The ethanol injection method is commonly used to produce liposomes, due to its simplicity, ease of scale-up, and safe production technique.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study of entrapment efficiency of hydrophobic drugs, which were teicoplanin and rifampicin in liposomes prepared by the conventional thin film method. The maximum entrapment efficiency of teicoplanin and rifampicin were 23.4% and 15.5%, respectively [ 24 ]. It is suggested that the low entrapment efficiency of the drug might result from the conventional method preparation.…”
Section: Resultsmentioning
confidence: 99%
“…The encapsulation efficiency in delivery systems usually refers to the amount of drug i.e., pure bioactive compound encapsulated in the system [ 45 ].…”
Section: Methodsmentioning
confidence: 99%